Supply Chain Management and Competitive Advantage in Pekanbaru City: An Evidence from Small and Medium-Sized Bread Industry - Prima Andreas Siregar; Pegy Tasia Ganeha; Restu (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
The purpose of this research is to look at the effects of supply chain management and competitive advantage on the performance of Pekanbaru City's small and medium-sized baking industries. In this investigation, the sample was drawn using a non-probability sampling method known as saturation sampling. The questionnaire was distributed to employees or owners of Pekanbaru City's small and medium-sized baking enterprises. Sixty-seven employees or business owners from Pekanbaru City's small and medium-sized bread industries were included in the sample population. The acquired data were analyzed using the PLS (Partial Least Squares) analytic technique with SEM-PLS and WarpPLS 6.0 software. According to the findings, supply chain management positively impacts firm performance. Supply chain management can also help to gain a competitive advantage. Furthermore, competitive advantage has a beneficial effect on firm performance, and supply chain management affects company performance whether or not it has a competitive advantage, though it tends to have a direct effect.